APLIKASI PRESENSI DAN PENGGAJIAN BERBASIS WEB (STUDI KASUS: CV. KARYA KOBA JAYA) - Enirianti, Enirianti; Andry, Johannes Fernandes (ISTEK WIDURI, 2022)
Because many jobs exist, companies use information technology to help with office work. Employee attendance is related to the performance and discipline of employees in the company and is important for the company. CV. Karya Koba Jaya is a company engaged in the construction of buildings, bridges, roads, and irrigation. Problems that exist in the company are long attendance processes due to long lines, leave applications that must meet HRD directly and there is no record of leave information and slow payroll processes because they must be adjusted to attendance data and the long attendance data recapitulation process so that it hampers payroll process. This attendance application, leave application, and payroll can solve employee problems in absenteeism, leave application, and payroll. This web-based application for leave and payroll attendance requires PHP language and the waterfall model SDLC method with stages such as needs analysis, system design, implementation, testing, and maintenance to make a system as expected. The results of this study indicate that the attendance application for submitting leave and payroll based on this website can help employees in attendance, apply for leave, and payroll and can help the attendance recapitulation process can be fast so that the payroll process is not hampered. And the test results from the application that show attendance applications, leave applications, and website-based payroll are all functioning well without any problems or errors in the application so that it can be implemented in the organization. The conclusion of this study is that this website-based application for absenteeism and payroll applications can help overcome problems that exist in the company.